Kurikulum Merdeka in Informatics subjects at vocational high schools - Adelia Nur Fitriana (Hipkin Journal of Educational Research, 2026)
Vocational education in Indonesia is currently transforming by strengthening the relevance of learning to the world of work through the implementation of the Kurikulum Merdeka. This study aims to explore how the Kurikulum Merdeka is implemented in Informatics subjects at SMKN 1 Majalengka. Using a descriptive qualitative approach, data were collected through in-depth interviews with Informatics teachers and the school's curriculum development team. Specific findings at SMKN 1 Majalengka indicate that teachers utilize the flexibility of the Kurikulum Merdeka to independently develop teaching tools such as Capaian Pembelajaran (CP), Tujuan Pembelajaran (TP), Alur Tujuan Pembelajaran (ATP), and teaching modules tailored to student needs and industry demands. The curriculum development procedure at this school is carried out systematically by the Tim Pengembang Kurikulum (TPK), which involves the principal, the vice principal for curriculum, the subject teacher coordinator, the Guidance and Counseling teacher, the school committee, education experts, and representatives from the education office. Curriculum revision activities are carried out annually through the In-House Training (IHT) forum. The main challenges identified in the field include limited resources, particularly budget and supporting facilities, as well as minimal industry involvement in the curriculum development stage.    Abstrak Pendidikan vokasi di Indonesia saat ini tengah mengalami transformasi melalui penguatan relevansi pembelajaran dengan dunia kerja melalui implementasi Kurikulum Merdeka. Studi ini bertujuan untuk mengeksplorasi bagaimana Kurikulum Merdeka diimplementasikan pada mata pelajaran Informatika di SMKN 1 Majalengka. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara mendalam dengan guru Informatika dan tim pengembang kurikulum di sekolah. Temuan spesifik di SMKN 1 Majalengka menunjukkan bahwa fleksibilitas Kurikulum Merdeka dimanfaatkan oleh guru untuk mengembangkan secara mandiri perangkat ajar seperti Capaian Pembelajaran (CP), Tujuan Pembelajaran (TP), Alur Tujuan Pembelajaran (ATP), dan modul ajar yang disesuaikan dengan kebutuhan murid dan tuntutan industri. Prosedur pengembangan kurikulum di sekolah ini dilakukan secara sistematis oleh Tim Pengembang Kurikulum (TPK) yang melibatkan kepala sekolah, wakil kepala sekolah bidang kurikulum, koordinator guru mata pelajaran, guru Bimbingan Konseling, komite sekolah, pakar pendidikan, dan unsur dinas pendidikan, dengan kegiatan revisi kurikulum dilakukan secara rutin setiap tahun melalui forum In House Training (IHT). Tantangan utama yang teridentifikasi di lapangan meliputi keterbatasan sumber daya, khususnya anggaran dan fasilitas pendukung, serta minimnya keterlibatan industri dalam tahap penyusunan kurikulum. Kata Kunci: kurikulum merdeka; mata pelajaran informatika; pendidikan vokasi